2011
DOI: 10.1039/c1ra00647a
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid modified cellulose whiskers

Abstract: L-Leucine amino acid functionalized cellulose whiskers were synthesized via esterification reaction which comprised the reaction between Fmoc-L-leucine and cellulose whiskers and removal of Fmoc-protecting group. This strategy provides a direct, facile way to merge the properties of these biocompatible materials and offers the possibility to introduce biologically active building blocks in cellulose whiskers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 51 In 2011, Cateto et al modified cellulose nanowhiskers with L-leucine by a two-step process involving the reaction between CNCs and Fmoc-protected L-leucine followed by the removal of the Fmoc protecting group. 52 The reaction was performed with 4-dimethylaminopyridine (DMAP) as a base catalyst and N-ethyl-N’-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC HCl), as a coupling agent.…”
Section: Surface Chemistry Of Nanocellulosementioning
confidence: 99%
“… 51 In 2011, Cateto et al modified cellulose nanowhiskers with L-leucine by a two-step process involving the reaction between CNCs and Fmoc-protected L-leucine followed by the removal of the Fmoc protecting group. 52 The reaction was performed with 4-dimethylaminopyridine (DMAP) as a base catalyst and N-ethyl-N’-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC HCl), as a coupling agent.…”
Section: Surface Chemistry Of Nanocellulosementioning
confidence: 99%
“…No noticeably cytotoxic effect was observed, rendering modified cellulose nanocrystals as promising candidates for bioimaging and drug delivery systems. Anchoring of L-leucine moieties to cellulose nanocrystals allowing the creation of a binding site to which drugs or targeting molecules can be attached was also reported (Cateto and Ragauskas, 2011). TEMPO-oxidized MFC was coupled with fluorescent amino acids using a two-step procedure (Barazzouk and Daneault, 2011).…”
Section: Fluorescently Labeled Nanocellulosementioning
confidence: 99%
“…These modifications are beneficial in a variety of medical applications, in particular as wound dressing materials. Cateto et al [21] reported the functionalisation of BC with L-leucine using Fmoc-L-leucine and cellulose whiskers to enhance cell-adhesive structures, hydrophobic drug carriers and gas separation membranes. Kalaskar et al [17] reported the characterisation of cellulose fibre surfaces by modification using three different amino acids with variable side chain groups using solid phase peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%